2004
DOI: 10.1158/1078-0432.ccr-04-0493
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Parafibromin Immunoreactivity Is a Distinguishing Feature of Parathyroid Carcinoma

Abstract: Purpose: A reliable method for diagnosing parathyroid carcinoma has remained elusive over the years, resulting in its under-recognition and suboptimal therapy. Obtaining an accurate diagnosis has become an even more pressing matter with recent evidence that germline HRPT2 gene mutations are found in patients with apparently sporadic parathyroid carcinoma. There is a high prevalence of HRPT2 gene mutations and biallelic inactivation in parathyroid carcinoma. We hypothesize that loss of parafibromin, the protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
166
1
8

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(184 citation statements)
references
References 44 publications
9
166
1
8
Order By: Relevance
“…The nuclear localization of parafibromin is in agreement with the results of three other studies (Tan et al, 2004;Hahn and Marsh, 2005;Rozenblatt-Rosen et al, 2005). Parafibromin is a 61 kDa protein, and it has been reported that proteins with a molecular mass >45 kDa cannot diffuse freely across the nuclear envelope and require to be actively transported through the nuclear pore complex via a process that involves recognition by the importins of NLSs in the proteins (Quadrini and Bieker, 2002;Vandenbroucke et al, 2004).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The nuclear localization of parafibromin is in agreement with the results of three other studies (Tan et al, 2004;Hahn and Marsh, 2005;Rozenblatt-Rosen et al, 2005). Parafibromin is a 61 kDa protein, and it has been reported that proteins with a molecular mass >45 kDa cannot diffuse freely across the nuclear envelope and require to be actively transported through the nuclear pore complex via a process that involves recognition by the importins of NLSs in the proteins (Quadrini and Bieker, 2002;Vandenbroucke et al, 2004).…”
Section: Discussionsupporting
confidence: 90%
“…Thus, as part of this protein complex, parafibromin may regulate posttranscriptional events and histone modification. In keeping with such roles parafibromin has been reported to be a nuclear protein by two studies (Tan et al, 2004;Rozenblatt-Rosen et al, 2005), although one other study has reported that parafibromin may also be in the cytoplasm (Woodard et al, 2004).…”
Section: Introductionmentioning
confidence: 89%
“…Most parathyroid carcinomas also exhibit aberrant immunohistochemical staining for parafibromin, the protein product of CDC73; complete loss of parafibromin expression is the most common staining pattern. As the large majority of benign parathyroid tumors (except in the setting of germline CDC73 mutation) display normal parafibromin staining, parafibromin immunohistochemistry may be considered as a diagnostic adjunct for parathyroid cancer in otherwise equivocal cases [22][23][24] but aberrant parafibromin staining alone is insufficient as a diagnostic marker of parathyroid carcinoma [25] .…”
Section: Cdc73mentioning
confidence: 99%
“…Expression of parafibromin is lost in between 70 and 90% of both syndromic and sporadic parathyroid carcinomas [43][44][45]. Parafibromin is almost always preserved in histologically and clinically benign parathyroid adenomas [46].…”
Section: Parathyroid Carcinoma: Illustration Of a Tumor Suppressor Genementioning
confidence: 99%